A Randomized Prospective Study of Short-Term Complications Between Simple Release and Extensor Retinaculum Reconstruction in De Quervain’s Tenosynovitis - Chusing, Natdanai (Journal of Southeast Asian Orthopaedics, 2024)
Purpose: To study and compare the postoperative complications of De Quervain’s tenosynovitis treatment using two methods: simple release and extensor retinaculum reconstruction. Methods: This randomized controlled trial included 24 patients divided into two groups: Group 1 (simple release) and Group 2 (extensor retinaculum reconstruction), with 12 patients in each group. Results: The mean age of the participants was 51.75 and 49.25 years for Groups 1 and 2, respectively. The study participants included three males and 21 females. Intraoperatively, subcompartments were observed in two patients in Group 1 and six patients in Group 2. Additionally, a ganglion cyst in the tendon was found in one patient per group. The mean preoperative visual analog scale (VAS) and Disabilities of the Arm, Shoulder and Hand (DASH) scores for Group 1 were 7.83 and 61.44, respectively, whereas those for Group 2 were 8.17 and 66.52, respectively. Postoperatively, the VAS and DASH scores for Group 1 changed to 2.17 and 15.47, respectively, whereas those for Group 2 changed to 2.67 and 16.33, respectively (p = 0.843 and 0.63, respectively). Tendon subluxation was observed in two patients in Group 1, with none in patients in Group 2 (p = 0.14). Conclusions: No significant tendon subluxation was observed in either surgery type, with no significant differences in the treatment outcomes.